New record and range extension of the primnoid octocoral Verticillata castellviae in the Southwest Atlantic Ocean - Schejter, Laura (2021)
In this study we report the presence of the soft coral Verticillata castellviae (Zapata-Guardiola, López-González & Gili, 2013), off Buenos Aires, Argentina, at 947m, which constitutes the northernmost record for this species. It was collected as a bycaught species with a troncopyramidal trap during an experimental cruise devoted to the study of the red crab Chaceon notialis and the Patagonian lobsterette Thymops birsteini.